Antiproliferative activity of withanolides against human breast cancer cell lines - Machín, Rubén (2010)
The in vitro antiproliferative activity of a series of 22 naturally occurring withanolides was examined against the T-47D, MCF7, MCF7/BUS, MDA-MB-231, and SK-Br-3 human solid tumor breast cancer cell lines. The most active compound showed GI(50) values in the range 0.16-0.71 muM. The aromatic withanolide 19 exhibited specific activity for the estrogen-receptor-positive cell lines (T-47D, MCF7, and MCF7/BUS). Overall, the results demonstrated the relevance of the substitution pattern on the A and B rings on the resultant antiproliferative activity.